Предмет:
АлгебраАвтор:
calebwrightf(x) = 6cosx + 2sinx, x₀ = π/4
f'(x) = -6sinx + 2cosx
f'(x₀) = f'(π/4) = -6sin(π/4) + 2cos(π/4) = -6 · √2/2 + 2 · √2/2 = -3√2 + √2 = -2√2
Ответ-2√2
Автор:
katherineНайдём производную f'(x)
Подставим в f'(x) x = π/4
Ответ:
Автор:
fernandauho9Добавить свой ответ
Предмет:
Английский языкАвтор:
zaidenschmittОтветов:
Смотреть
Предмет:
МатематикаАвтор:
gilbertОтветов:
Смотреть
Предмет:
БиологияАвтор:
joaquinlucasОтветов:
Смотреть
Предмет:
Английский языкАвтор:
dolcewi43Ответов:
Смотреть